Isolation and identification of efficient Egyptian malathion‐degrading bacterial isolates. (21st June 2013) - Hamouda, S. A.; Marzouk, M. A.; Abbassy, M. A.; Abd‐El‐Haleem, D. A.; Shamseldin, Abdelaal
<x xml:space="preserve">Abstract</x> Bacterial isolates degrading malathion were isolated from the soil and agricultural waste water due to their ability to grow on minimal salt media amended with malathion as a sole carbon source. Efficiencies of native Egyptian bacterial malathion‐degrading isolates were investigated and the study generated nine highly effective malathion‐degrading bacterial strains among 40. Strains were identified by partial sequencing of 16S rDNA analysis. Comparative analysis of 16S rDNA sequences revealed that these bacteria are similar with the genus Acinetobacter and Bacillus spp. and RFLP based PCR of 16S rDNA gave four different RFLP patterns among strains with enzyme HinfI while with enzyme HaeI they gave two RFLP profiles. The degradation rate of malathion in liquid culture was estimated using gas chromatography. Bacterial strains could degrade more than 90% of the initial malathion concentration (1000 ppm) within 4 days.